Pergeseran Faktor Psikologi Penentu Keputusan Pembelian (Studi Kasus Sayuran Organik Di Pasar Modern Kota Palembang): - Dessy Adriani; Yandri Ridho Pratama; Laila Husin (Politeknik Negeri Lampung., 2021)
Abstract Increased awareness of the importance of health is also thought to have an impact on the consumption behavior of organic vegetables. So far, more research on purchasing decisions has been analyzed with consideration of microeconomic theory. Along with the development of information and knowledge, purchasing decisions are thought not only to be economic decisions but also to psychological considerations, especially the determinant factors. This research was carried out in the modern market of Palembang city. The research method was a survey method and the sampling method was an accidental sampling technique. Data analysis using Factorial Multivariate Analysis. The results of the analysis show psychological factors that influence purchasing decisions in terms of the importance level are (1) Perception, (2) Learning, (3) Attitudes, and (4) consistency. The analysis results differ with the level of theoretical importance. The level of importance based on the analysis are (1) motivation, (2) perception, (3) learning, and (4) attitude. The results of this study indicate that motivation is no longer a psychological factor in purchasing decisions, and there is a shift in factors where perception is the first and most important determining factor.